Pengaruh Harga Psikologis, Desain Produk, dan Citra Merek terhadap Minat Beli Perempuan pada Merek Pencuci Piring - Anita Sain; Simon Sia Niha; Maria Augustin Lopes Amaral (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2023)
The purpose of this study was to determine the effect of psychological price, product design, and brand image on the intention to buy Mama Lemon dishwashing soap in Kupang district. The population in this study were all women using Mama Lemon dishwashing soap in Kupang Regency, and the research samples were women who had used Mama Lemon dishwashing soap in Kupang Regency for at least one year. This study uses a convenience sampling technique, namely sampling; technique based on the convenience factor. The results showed that price, product design and brand image had an effect on purchasing decisions for Mama Lemon dish soap in Kupang district.